The Relation between ACE Gene Polymorphism and the Severity of COVID-19 Infection - El-Sayed Marei, Yara; Abdallah Bayoumy, Ahmed; Mohamed Abulazm Nassar, Hassnaa; Mansour, Bassam; Bakeir Hamady, Asmaa (International Journal of Microbiology, 2023)
Introduction. The coronavirus disease 2019 (COVID-19) pandemic, which emerged in China at the end of 2019, rapidly spread worldwide. The angiotensin-converting enzyme (ACE) gene contains an insertion/deletion (I/D) polymorphism that leads to a higher serum ACE level which is associated with several diseases and also with a high mortality rate in SARS. Therefore, this study aimed at assessing the association between ACE gene polymorphism and the risk and severity of COVID-19 disease in patients. Methodology. Forty-five SARS-CoV-2 infected patients and another random control group of 45 healthy individuals were included. The detection of ACE I/D gene polymorphism in both groups was done by PCR. Results. 53% of infected patients with SARS-CoV-2 had an ACE deletion/deletion genotype (D/D), 27% had an ACE deletion/insertion genotype (D/I), and 20% had an ACE insertion/insertion genotype (I/I). On the one hand, the D/D variant was significantly detected in the COVID-19 patients compared to the control subjects, whereas the I/I variant was significantly detected in the control subjects compared to the COVID-19 patients (p = 0.004). The D/D variant subgroup showed the lowest lymphocytic count compared to the D/I or I/I subgroups. In addition, the C-reactive protein was significantly higher and the oxygen saturation was significantly lower in patients with the D/D allele compared to the other subgroups. Conclusions. ACE gene polymorphism, particularly the DD genotype, was observed to affect the severity of COVID-19 infection.